Dual-energy CT colonography for preoperative "one-stop" staging in patients with colonic neoplasia - Schaeffer, Benno; Johnson, Thorsten R C; Mang, Thomas; Kreis, Martin E; Reiser, Maximilian F; Graser, Anno (Academic radiology, 2014)
To evaluate the benefits of dual-energy computed tomography (CT) colonography (DECTC) as a preoperative staging tool in patients with clinically suspected colorectal cancer (CRC). Twenty-two patients with colorectal neoplasia underwent preoperative abdominal DECTC on a dual-source scanner (SOMATOM Definition Flash; Siemens) operated at tube potentials of Sn140/100 kVp. Scans were evaluated for local tumor stage and the presence of synchronous intracolonic and extracolonic findings using dual-energy color-coded images. An enhancement ≥25 Hounsfield units (HU) was defined to indicate malignancy. Patients' effective doses were calculated. Preoperative DECTC allowed for complete bowel evaluation in all patients, including subjects with stenosing CRC. DECTC revealed 22 carcinomas (mean enhancement, 47 ± 12 HU). In total, 22 synchronous intracolonic lesions were detected, including 19 adenomas (mean enhancement, 51 ± 19 HU). Benign structures showed enhancement <25 HU. Comparing DECTC to histopathology, 95% carcinomas and 71% synchronous lesions proximal to stenosing CRC could be verified. Mean estimated effective dose was 13.0 ± 5.2 mSv. Preoperative DECTC can be used as an accurate and dose-efficient primary-staging examination. Especially after incomplete optical colonoscopy, virtual colonoscopy enables full preoperative colonic assessment on the same day. Dual-energy CT enables distinction between neoplasia and non-neoplastic findings within and outside the colon. Therefore, DECTC can be regarded as a promising "one-stop" staging examination in patients with clinically suspected CRC.